Ashqelon Barneʻa : the Early Bronze Age site. - Golani, Amir (IAA reports, 2022)
Ashqelon Barne'a the Early Bronze Age Site, Volume II, the Finds (IAA reports 70), is the second of two volumes comprising the complete and final report of the three excavation seasons at the Early Bronze Age I site of Ashqelon Barne'a that took place in 2004 and 2005. Volume I (IAA Reports 65) includes an introduction to the excavations, the geographical and geomorphological setting, the stratigraphy, architecture and settlement planning, radiocarbon (14C) dating and an appendix concerning Byzantine remains. Volume II , the finds, is comprised of thirteen chapters and includes a full presenta.